PENTINGNYA KOMUNIKASI DAN KERJASAMA TIM TERHADAP SISWA SMK KARANG ANYAR KEBUMEN JAWA TENGAH - Winata, Hadi; Sartika, Dewi; Purni Hernawati, Sri (Jurnal Pengabdian Tangerang Selatan [JURANTAS], 2026)
The Community Service Program (PKM) aims to improve the understanding and skills of students of SMK Karang Anyar, Kebumen, Central Java, regarding the importance of communication and teamwork in the world of work. In the era of the industrial revolution 4.0 and society 5.0, communication and collaboration skills are key competencies that determine the success of vocational school graduates in the world of work. This study uses a qualitative approach with lecture methods, group discussions, and teamwork simulations to measure students' understanding and practice. Data were collected through observation, in-depth interviews, and focus group discussions with 45 students in grades XI and XII. The results showed a significant improvement in students' understanding of effective communication, with 87% of students able to identify elements of good communication, and 82% of students showing improved teamwork skills in project-based learning simulations. This PKM activity makes a real contribution to improving the soft skills of vocational school students who will enter the industrial world. The long-term implications of this program are to increase the competitiveness of vocational school graduates and contribute to the achievement of the Sustainable Development Goals (SDGs), especially in quality education and decent work